Pembinaan Dan Overcrowded Di Lembaga Pemasyarakatan - Ahmad Agung Raharjo; Mitro Subroto (Widya Yuridika, 2022)
A citizen who commits a criminal crime and is proven guilty until he has legal force will continue to serve the crime of missing independence in prison. Broadly speaking, this is a criminal justice system in Indonesia where because the system does not adapt to the development of the times and conditions in the field, this is making prisons as a post-final punishment for being overcrowded (excess occupants) and coaching does not run optimally based on the reasons above, this underlies the existence of the CBC concept, which is a type or alternative punishment program that is coaching in Indonesia, the concept is carried out when prisoners will serve the rest of their crimes with the concept of blending them into the community with certain conditions and supervision. This study aims to determine the extent to which the effectiveness of the role of CBC on coaching and overcrowded in prisons. This research method uses descriptive qualitative research by means of library research, namely by taking data from journal literature, documents, news and books that are relevant to the research core. The results of this study are that the CBC concept is very effective in helping overcrowded prisons and the coaching model is quite good even though there are obstacles in its implementation, such as not optimal infrastructure for inmates and obstacles in collaborating with 3rd parties as a place for the CBC implementation process. But this is worth the positive impact that is better with the application of this concept